Pedagogical Approaches in Computational Thinking-Integrated STEAM Learning Settings: A Literature Review - Veerasamy Ashok Kumar; Larsson Peter; Apiola Mikko-Ville; D'Souza Daryl; Laakso Mikko-Jussi (Switzerland, 2022)
This paper aims to provide a comprehensive analysis of pedagogical approaches deployed in computational thinking (CT)-based STEAM curricula during the period 2015–early 2020. Based on a set of suitable search keys for querying the Scopus database we found 46 studies on CT-integrated STEAM learning settings in K-12 schools and universities. Nearly 46% of the studies were in K-12 science learning. Seven different pedagogies were used to introduce CT in STEAM (science, technology, engineering, arts and mathematics) environments. Collaborative learning, hands-on and learning by modelling activities, were found to be the main approaches in CT-integrated STEAM learning research settings. In addition, most of these studies used computing principles to teach CT + STEAM topics. However, the roles of pedagogies used in these studies were not clearly stated. Furthermore, CT principles in STEAM learning were not well-defined. Hence, our study provides evidence that it is critical to develop a possible inventory of successful pedagogies and supporting learning activities for CT-integrated learning environments.
Intelligent Computing: Proceedings of the 2021 Computing Conference, Volume 3